Promosi Budaya dan Potensi Wisata Alam dalam Rangka Meningkatkan Pengembangan Pariwisata Desa Ngargosari, Samigaluh, Kulonprogo, DIY - Yendrawati, Reni; Hinggis, Bara Hasnuagi (Jurnal Hasil Pengabdian kepada Masyarakat Universitas Jember, 2023)
As an archipelagic country, Indonesia has a lot of potential in developing natural tourism. The tourism industry is slowly crawling along with the acceleration of tourism development on the government's current agenda. Indonesia has provinces that are rich in tourism potential, one of which is the Kalurahan/Ngargosari Village area, Samigaluh District, Kulon Progo Regency. Tourist destinations in this area include Puncak Widosari, Rajendra Farm, Kyiai Aliyan Hut, Jathilan Arts, Bangilun Arts, Gatoloco Education, Kemadon Tea Garden Education, and Cip janggel corn cob crafts. Apart from that, there is another untouched potential, Kedung Bawi. The management of tourist destinations is handed over by the village to the Tourism Village administrators who have at least carried out promotional activities in order to introduce the Ngargosari Village tourism series to the general public. However, these efforts still have gaps that hinder the realization of the Ngargosari Tourism Village as a favorite tourist destination.